Notes on Early Land Plants Today. 27. Transfer of some taxa from Stenolejeunea (Lejeuneaceae, Marchantiophyta) - Renner, Matt A. M.; Pócs, Tamás; Söderström, Lars; Hagborg, Anders; Konrat, Matt Von (Phytotaxa, 2013)
Stenolejeunea Schuster (1963: 144), a small genus of Lejeuneaceae subf. Lejeuneoideae containing seven described species, was recently synonymised with Lejeunea Libert (1820: 373) by Gradstein (in Söderström et al. 2010) and the three taxa occurring on Java (including the type of the genus) were transferred. A fourth New Zealand taxon was transferred by Renner & de Lange (2011). However, three taxa remain to be transferred, two of which need new names in Lejeunea.